Energy production and C02 emisson efficiency of eight European countries in the manufacturing area - Murillo, Kelly P. (2018)
An energy efficiency comparison of manufacturing sectors of eight European countries, between 2008-2013, is performed in order to understand how the world economical crisis affected theirperformance. The analysis rely in a combination of multidirectional efficiency analysis blended with other techniques, as nc-value, principal component analysismixed with a dimensionality test.The purpose is to analyse three different approaches organized by: (a) a general viewpoint on countries/sectors; (b) sectors and inefficiency input usage; and (c) intensive versus non-intensive energy sectors. We also consider non-normalized and normalized data, by the total number of firms. The results indicate that the great majority of sectors/countries analyzed show a decrease in the CO2 emissions. Since thecalculated inefficiency indexes expose the sectors which used inputs in excess, we found that the most efficient sectors were: basic metals; rubber and plastic products, products of wood and cork; textiles, wearing apparel and of leather products; whereas chemical products and food;beverages and tobacco products were the most inefficient sectors. Our approach also give indicators about the way each sector/country was affected by the crisis and how they were able to react or adapt to it.